2020
DOI: 10.3390/su12062502
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Agritourism Activity. Initiatives and Challenges in Romanian Mountain Rural Regions

Abstract: Sustainability has become a priority in the last decades. If we consider rural regions, agritourism, an activity strongly related to local communities, represents an opportunity to ensure the sustainability of rural settlements and of the environment, and at the same time an innovative and diversifying possibility for the economic support of rural settlements. Many studies have shown that the sustainability trend of the current period can be achieved by combining rural and local resources and traditional produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 35 publications
0
30
0
4
Order By: Relevance
“…It is noteworthy that the sustainability of rural tourism is based on the idea of combining the social and economic interests of rural areas and the interests of the natural environment. Combining rural and local resources and traditional products that are unique to rural areas with tourism activities can facilitate the current trend of sustainable development [13].…”
Section: Rural Revitalization and Smart Specialization: New Opportunimentioning
confidence: 99%
“…It is noteworthy that the sustainability of rural tourism is based on the idea of combining the social and economic interests of rural areas and the interests of the natural environment. Combining rural and local resources and traditional products that are unique to rural areas with tourism activities can facilitate the current trend of sustainable development [13].…”
Section: Rural Revitalization and Smart Specialization: New Opportunimentioning
confidence: 99%
“…The low percentage of the owners of agritourism structures who declared that, in order to coordinate the activity, they have benefited from aid, in fact they referred to the accounting and sales/capitalization part of the agritourism products. In fact, a previous study [29] showed that the owners of agritourism structures, from the two areas do not have specialized training in the field, so in other terms they need help for certain stages of the activity, especially in terms of the creation and capitalization of the agritourism product.…”
mentioning
confidence: 99%
“…The poor sustainability of agritourism growth was also found in a large proportion of the central and eastern regions of Spain, the largest group of regions in Spain (Group C), and is comparable with that of Italy. Some policymakers may have increasingly and uncritically invested in the "utilities" of agritourism, more due to superficial rhetoric [47,[115][116][117][118][119] than out of any meaningful concern for sustainability [29,40,120,121]. In this situation, the SSI offers new parameters for evaluating the status quo and for drafting policies aimed at diversifying agriculture through tourism.…”
Section: Discussionmentioning
confidence: 99%